Performing and dying in the name of world peace: From metaphor to real life in feminist performance - (:unkn) unknown (Aesthetics Media Services, 2010)
The paper presents an analysis of "Brides on Tour" undertaken by the Italian performance artists Pippa Bacca and Silvia Moro on International Women's Day (8th March) in 2008 and considers it as much as a symbolic act of sacrifice, performing for global politics as potent subject and woman as victimized object of local 'petty crime'. A very important aspect of the performance is the way it blurs certain boundaries, as with feminist activity in general. In the performance, the writer detects a sense of solidarity by women for women on a global level, where the sacrifice reflected in the risk-taking aspect of hitchhiking symbolizes the past efforts of feminist activists who have at times put their lives in danger to better the living conditions of women through the ages and across nations.
Keywords: Brides on tour; Feminist; Performance; Pippa Bacca